2017
DOI: 10.1097/imi.0000000000000391
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Repair of Peripheral Arterial Disease

Abstract: Objective One thousand consecutive patients who underwent endovascular repair in an 8-year period were studied retrospectively to evaluate technical success, freedom from reinterventions, early clinical outcome, and risk factors for restenosis/occlusion. Methods Mean ± SD Rutherford class was 3.29 ± 0.8. A total of 755 patients have claudication, 423 from rest pain, and 569 from ischemic ulceration. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…The rates of major amputation and the need for reintervention were similar across the two groups, but, as indicated previously, the location of lesions and type of angioplasty in women were somewhat different. Although our research lacked the power to properly support a negative correlation due to its relatively small sample size, our findings are in line with other larger studies, which also failed to show a correlation between gender and MALE over time [ 8 ]. Orr et al investigated 104 angioplasties, and there was no significant difference in the outcomes between men and women [ 17 ].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The rates of major amputation and the need for reintervention were similar across the two groups, but, as indicated previously, the location of lesions and type of angioplasty in women were somewhat different. Although our research lacked the power to properly support a negative correlation due to its relatively small sample size, our findings are in line with other larger studies, which also failed to show a correlation between gender and MALE over time [ 8 ]. Orr et al investigated 104 angioplasties, and there was no significant difference in the outcomes between men and women [ 17 ].…”
Section: Discussionsupporting
confidence: 83%
“…A meta-analysis using the National Inpatient Sample (NIS) database concluded that women have similar in-hospital mortality compared to men, who are more likely to develop periprocedural complications such as acute renal failure, gangrene or infections [ 7 ]. Another study published in 2017 describing the mid-term results of endovascular therapy of more than 1000 subjects (45% women) did not identify significant differences related to the subjects’ gender regarding one-year patency of endoprostheses [ 8 ]. Variables such as sex, age, diabetes, hypertension, dyslipidemia, or cerebrovascular disease were not predictors for restenosis or occlusion in the short and medium term.…”
Section: Introductionmentioning
confidence: 99%